PER3 and ADORA2A polymorphisms impact neurobehavioral performance during sleep restriction. (21st November 2012) - Rupp, Tracy L.; Wesensten, Nancy J.; Newman, Rachel; Balkin, Thomas J.
Summary The objective of the study was to determine whether ADORA2A or PER3 polymorphisms contribute to individual responsivity to sleep restriction. Nineteen healthy adults (ages 18–39, 11 males, 8 females) underwent sleep restriction (SR) which consisted of seven nights of 3 h time in bed (TIB) (04:00–07:00). SR was preceded by seven in‐laboratory nights of 10 h TIB (21:00–07:00) and followed by three nights of 8 h TIB (23:00–07:00). Volunteers underwent psychomotor vigilance, objective alertness, and subjective sleepiness assessments throughout. Volunteers were genotyped for the PER3 VNTR polymorphism (PER34/4n = 7; PER34/5n = 10; PER35/5n = 2) and the ADORA2A c.1083T>C polymorphism, (ADORA2AC/Tn = 9; ADORA2AT/Tn = 9; ADORA2AC/Cn = 1) using polymerase chain reaction (PCR). Separate mixed‐model anovas were used to assess contributions of ADORA2A and PER3 polymorphisms. Results showed that PER34/4 and ADORA2AC/T individuals expressed greater behavioral resiliency to SR compared to PER4/5and ADORA2AT/T individuals. Our findings contrast with previously reported non‐significant effects for the PER3 polymorphism under a less challenging sleep restriction regimen (4 h TIB per night for five nights). We conclude that PER3 and ADORA2A polymorphisms become more behaviorally salient with increasing severity and/or duration of sleep restriction (based on psychomotor vigilance). Given the small sample size these results are preliminary and require replication.